2012
DOI: 10.2174/1573406411208061003
|View full text |Cite
|
Sign up to set email alerts
|

Antimitotic Activity on Sea Urchin Embryonic Cells of Seven Antiparasitic Morita-Baylis-Hillman Adducts: A Potential New Class of Anticancer Drugs

Abstract: In the present work we described improvements in the 1-7 antiparasitic Morita-Baylis-Hillman Adducts synthesis and their antimitotic activity on sea urchin embryonic cells. The 2-[Hydroxy(2-nitrophenyl)methyl]acrylonitrile (1) and 2-[Hydroxy(4-bromophenyl) methyl]acrylonitrile (4) were the most effective compounds to block the progression to embryonic morula stage (EC(50) = 75.8 μM and 72.6 μM, respectively). Compounds 1 and 4 were also effective in blocking the first cell division but to a lesser extent. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A2CN (3-hydroxy-2-methylene-3-(4-nitrophenyl)-propanenitrile), A3CN (3-hydroxy-2-methylene-3-(3-nitrophenyl)-propanenitrile), and A4CN (3-hydroxy-2-methylene-3-(2-nitrophenyl)-propanenitrile) (>99% pure) were synthesized and provided as described previously [21]. A 20 mM stock solution of A2CN, A3CN, and A4CN was prepared with dimethyl sulfoxide (DMSO) and freshly diluted in culture media for all in vitro experiments and in the control condition, and cells were treated using only the vehicle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A2CN (3-hydroxy-2-methylene-3-(4-nitrophenyl)-propanenitrile), A3CN (3-hydroxy-2-methylene-3-(3-nitrophenyl)-propanenitrile), and A4CN (3-hydroxy-2-methylene-3-(2-nitrophenyl)-propanenitrile) (>99% pure) were synthesized and provided as described previously [21]. A 20 mM stock solution of A2CN, A3CN, and A4CN was prepared with dimethyl sulfoxide (DMSO) and freshly diluted in culture media for all in vitro experiments and in the control condition, and cells were treated using only the vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…The Morita-Baylis-Hillman adducts (MBHA) have been described as anticancer compounds [2022]. It has been published that some MBHA molecules exhibited antimitotic activity against sea urchin embryonic cells [21, 22], and recently, our group demonstrated that these molecules have anticancer potential [23]. …”
Section: Introductionmentioning
confidence: 99%
“…The sea urchin is an already well-established marine model organism for developmental biology studies, largely used in drug discovery research for the understanding of cell proliferation processes induced by natural compounds with antimitotic activity [ 18 , 19 ]. In the last two decades, many studies have demonstrated the activation, at the enzymatic and morphological level, of apoptosis in sea urchins [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%